(untitled) (Altre Modernità, 2025)
In 2024, the comic book version of the novel Il Deserto dei Tartari by Dino Buzzati (Sergio Bonelli Editore) was published with texts by Michele Medda and illustrations by Pasquale Frisenda. The present work aims to analyze the strategies adopted by the authors to adapt the content of the work to the genre of the comic. It will not be a comparative reading with the original but it will focus on the comic book version, commenting at first on the graphic choices of the authors regarding the format, colors and recurring patterns used. The proposal for interactive reading mentioned in the preface will then be analyzed to identify, without pretensions of exhaustiveness, the intertextual and intermedial references, explicit and implicit, scattered in the work, illustrating their role within the overall graphic project.